Effects of Nd : YAG laser irradiation on root canal dentin wall: A scanning electron microscopic study - Camargo, SEA; Valera, M. C.; Camargo, CHR; Fonseca, M. B.; Menezes, M. M. (Mary Ann Liebert, Inc., 2005)
Objective: the purpose of this study was to evaluate, by scanning electron microscopy (SEM), the effects of Nd:YAG laser irradiation applied perpendicular or parallel to the root canal dentin wall. Methods: Thirty human teeth were divided into two groups: Group A (20 roots), laser application with circular movements, parallel to the dentin root surface; and Group B (10 roots), roots cut longitudinally and laser applied perpendicular to the root surface. Group A was subdivided into A1 (10 roots), laser application with 100 mJ, 15 Hz and 1.5 W; and A2 (10 roots) with 160 mJ, 15 Hz, and 2.4 W. Group B was subdivided into B1 (10 hemisections) and B2 (10 hemi-sections) with parameters similar to A I and A2. Four applications of 7-sec duration were performed, with a total exposure of 28 sec. SEM evaluations were made in the cervical, middle, and apical thirds, with 500X and 2000X magnifications. Morphological changes scores were attributed, and the results were submitted to Kruskal Wallis statistical test (5%). Results: Significant statistical differences were found between groups A and B (p = 0.001). In groups A1 and A2, few areas of dentin melting were observed. In groups B1 and B2, areas of melting dentin covering dentin surface were observed. Conclusions: It was concluded that intracanal laser application with circular movements (parallel to the surface) produces limited morphological changes in root canal dentin wall.